(untitled) (Fiep Bulletin - online, 2012)
It is a qualitative study aims to learn about the concepts of professional medical error conducted with 46 professionals of both sexes, randomly selected in Campus I of the Federal University of Paraiba, in João Pessoa, Paraiba - Brazil. We identified the following concepts: medical error: the result of arrogance, egotism and arrogance, as a synonym of inattention, incompetence and disengagement, a result of centralization, domination and sovereignty, such as abuse and death as a synonym for human. The views of professionals about medical error refers to aspects of responsibility for both the physician and the health system itself, as obstacles experienced by users of health, which involves everything from medical, ethical and legal assistance to non-decent and equitable services health care they deserve, either publicly or privately.